2020
DOI: 10.3390/jof6030172
|View full text |Cite
|
Sign up to set email alerts
|

MrHex1 is Required for Woronin Body Formation, Fungal Development and Virulence in Metarhizium robertsii

Abstract: The Woronin body (WB) is a peroxisome-derived dense-core vesicle, a self-assembling hexagonal crystal of a single protein Hex1. This organelle is specific to the ascomycete fungi belonging to the Pezizomycotina subphylum by functioning in sealing septal pores in response to mycelium damage and the control of cell heterogeneity. We retrieved all available Hex1-domain containing proteins of different fungi from the GenBank database and found considerable length variations among 460 obtained Hex1 proteins. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 43 publications
1
31
1
1
Order By: Relevance
“…In the absence of Hex1, we observed reduced germination of conidia and growth rate upon treatment with either calcofluor white or Congo red, which indicates that changes in cell wall structure and related defects in hyphal integrity possibly result in impaired germination. Contrasting results have been reported as regards to the sensitivity of Δ hex1 mutant strains of other fungi to osmotic and cell wall/plasma membrane stress; deletion of the gene did not significantly affect M. robertsii and A. flavus [25,26], whereas in A. fumigatus and Arthrobotrys oligospora it had a significant impact [13,24].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In the absence of Hex1, we observed reduced germination of conidia and growth rate upon treatment with either calcofluor white or Congo red, which indicates that changes in cell wall structure and related defects in hyphal integrity possibly result in impaired germination. Contrasting results have been reported as regards to the sensitivity of Δ hex1 mutant strains of other fungi to osmotic and cell wall/plasma membrane stress; deletion of the gene did not significantly affect M. robertsii and A. flavus [25,26], whereas in A. fumigatus and Arthrobotrys oligospora it had a significant impact [13,24].…”
Section: Discussionmentioning
confidence: 88%
“…The major component of WBs was shown to be the conserved peroxisomal protein Hex1 in N. crassa [15,17]. Its discovery was followed by detailed analyses of its structure and functions, mostly in this and to a lesser extent in other fungi [13,16,18,20,26]. In this study, we identified the single Hex1 homolog of V. dahliae , a plant pathogen with a particularly broad range of hosts and significant economic impact [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An involvement for Woronin bodies during conidiation has been exposed in Fusarium graminearum (Gibberella zeae) , a devastating pathogen of cereals, where either the deletion or overexpression of HEX1 resulted in a significant reduction in conidiation [ 162 ]. Similarly, loss of Woronin bodies results in reduced conidiation in the nematophagous A. oligospora [ 163 ], in Aspergillus flavus [ 164 ] and the entomopathogenic M. robertsii [ 165 ], whereas in A. nidulans [ 166 ] and N. crassa [ 160 ] it has a minor impact in conidiation. Moreover, no visible conidiation defects are produced by Hex1 elimination in fungi like M. oryzae [ 167 ] and A. fumigatus [ 168 ].…”
Section: Woronin Bodies Specialized Peroxisome-derived Organellesmentioning
confidence: 99%